2019
DOI: 10.1371/journal.pone.0218669
|View full text |Cite
|
Sign up to set email alerts
|

Breaking down the barriers: Understanding migrant workers’ access to healthcare in Malaysia

Abstract: Background Malaysia is widely credited to have achieved universal health coverage for citizens. However, the accessibility of healthcare services to migrant workers is questionable. Recently, medical fees for foreigners at public facilities were substantially increased. Mandatory health insurance only covers public hospital admissions and excludes undocumented migrants. This study explores barriers to healthcare access faced by documented and undocumented migrant workers in Malaysia. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
118
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(123 citation statements)
references
References 26 publications
4
118
0
1
Order By: Relevance
“…Discrimination, too, has been reported elsewhere: two studies on minority populations in the United States (US) and a study on immigrants in Spain also highlights that these groups experienced discrimination within healthcare settings [ 26 , 29 , 30 ]. Another in-depth study conducted in Thailand found that Sub-Saharan African migrants living in Bangkok experienced a high level of dissatisfaction with the services provided by health professionals [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Discrimination, too, has been reported elsewhere: two studies on minority populations in the United States (US) and a study on immigrants in Spain also highlights that these groups experienced discrimination within healthcare settings [ 26 , 29 , 30 ]. Another in-depth study conducted in Thailand found that Sub-Saharan African migrants living in Bangkok experienced a high level of dissatisfaction with the services provided by health professionals [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…A few migrant workers in our study were not confident in Hindi or otherwise failed to understand the language used during their consultation. Other studies, too, have identified language as a barrier to accessing good-quality healthcare while working abroad [ 20 , 22 , 26 – 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sabah's migrant population, especially those who are refugees, from stateless minority groups and illegal or undocumented migrants face substantial challenges to accessing healthcare and social protectionincluding nancial, legal, language and physical access barriers. [19][20][21] The nding that non-citizens were signi cantly more likely to have advanced disease on chest X-ray and be sputum smear positive at presentation, supports the hypothesis that these groups face additional barriers to receiving timely diagnosis and treatment. We found that monthly household income of TB cases in Sabah (MYR 1000 or USD 250) was around one-quarter the median monthly household income across Sabah State (MYR 4110 or USD 1031 in 2016).…”
Section: Discussionmentioning
confidence: 77%
“…Anecdotally, migrants in both countries have reported discrimination by health providers [21,22]. Refugees also face significant difficulties accessing the health system.…”
Section: Introductionmentioning
confidence: 99%
“…Delayed healthcare seeking is associated with financial constraints in Malaysia [22], where migrant workers are required by the Ministry of Health to enrol in a private insurance scheme, the Hospitalization and Surgical Scheme for Foreign Workers (SPIKPA). However, the total coverage amount is low (20,000 Malaysian ringgit/USD 4,741) relative to foreigner fees charged in public hospitals (which saw 100% increases in 2016, linked to MOH budget constraints), and only documented migrants can enrol [30,31].…”
Section: Introductionmentioning
confidence: 99%